Challenges in implementing green urban space: from the lens of private developers / Muhammad Ikhwan Izzudin Weini ... [et al.] - Weini, Muhammad Ikhwan Izzudin; Mohamad Bohari, Asmah Alia; Adnan, Amira Shazlin; Wan Muhammad, Wan Mohd Nurdden; Savavibool, Nat (UiTM Press, 2022)
Urbanization should involve physical development such as the building itself and urban green space, a public space filled with plants. However, creating urban green space is not a priority by private developers which consider financial aspect and high-return developments that provide them with greater benefits. As a result, most modern urban development lacks urban green space, which impacts the character of urbanites' lifestyles. As a result, the goal of this study is to encourage private developers in Kuching to create urban green space. This research adopted a survey using questionnaires focusing on Kuching city. The result highlights the challenges of establishing urban green space from the perspective of private developers in Kuching. This outcome will add to the knowledge where the perception of private developers is being discussed. Future research should continue to explore ways of enhancing positive attitudes among private developers to enhance their engagement in urban green space.